Renovation of the Lapidarium in Kożuchów - Michalak, Bartosz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sacred monuments are an important part of the landscape of the Lubuskie region. Kożuchów, a small town some 30 km from the provincial capital Zielona Góra, is a town with a long and rich history, whose area is full of buildings in need of care. One of the important elements in its landscape is the museum of gravestone sculpture - the Lapidarium. The sepulchral lapidarium in Kozuchow is one of the best-preserved sets of tomb sculpture in Poland. It was established in the 1970s on the site of a former Protestant cemetery, for the establishment of which the Evangelical community received permission in 1634.
Keywords: Kożuchów (okręg) - architektura sakralna; lapidarium; historical monuments; sacred monuments; renovation; Lubuskie Region